Public perception of protected forested watershed area in Cameron Highlands, Malaysia - Empidi, Arlixcya Vinnisa (2020)
Intensive land-use changes are increasing in Cameron Highlands. Not only it caused massive forest conversion and land degradation, but it also poses significant environmental threats that could deteriorate the source of water resource, i.e., the forested watershed areas. The protection initiative can help in reducing the impact of land-use change and subsequently address environmental threats that undermine the sustainability of the forested watershed areas. The general objective of this study is to determine publics’ behavioural intention towards the protection initiatives for forested watershed areas in Cameron Highlands. The Theory of Planned Behaviour (TPB) was adapted to measure the determinants of publics’ behavioural intention. Hence the specific objectives are: (i) to examine the direct effect of TPB constructs (i.e., attitude, subjective norm, and perceived behavioural control) on public intentions towards the protection initiatives for forested watershed areas, and (ii) to investigate direct and indirect effects from external variables with the TPB constructs. Data collection employed the systematic random sampling and involved the face-to-face survey interview with 143 respondents in Ringlet, Tanah Rata, Brinchang, Terla and Tringkap of Cameron Highlands. The statistical analysis of Spearman’s rho correlation and multiple regressions analysis are applied in estimating the behavioural intention. The finding of this study shows the significant direct effect of attitude, in which the public have positive attitudes towards the protection initiatives for the forested watershed areas in Cameron Highlands. The direct effect of social norm also visible, where there are significant social pressures placed upon the public from their social circles, regarding their intention to participate in the protection initiatives. In the aspect of indirect effect, significant results of several proenvironmental behaviours show the essence of public behavioural beliefs and control beliefs that represent the intention of the public to participate in the protection initiatives. These pro-environmental behaviours include support conservation campaign, agreement on watershed conservation funds, belief in the good management of fertilisers and pesticides, attending sustainable agriculture practice seminars and accepting the improvement of manure plan. The other aspect of indirect effect such as the motivation to comply with the normative referents remains low, even though it is significant in influencing public intention. In general, the findings of this study indicate that attitude, subjective norms, and perceived behavioural control are significant predictors in examining the intention of the public to participate in the protection initiatives for forested watershed areas in Cameron Highlands. This study enriches the literature of TPB constructs in the context of forestry, through the understanding of publics’ perspective in protecting a critically important natural resource from the forest. It also provides timely and informative insights that will help government and relevant organisations to understand publics’ intention in protection initiatives. Consequently, it also could increase the involvement of the public in activities that safeguarding the forested watershed areas.